2014
DOI: 10.4103/1319-2442.139865
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cold ischemia time on delayed graft function and acute rejection in kidney transplantation

Abstract: The objective of this study is to evaluate the impact of cold ischemia time (CIT) on delayed graft function (DGF) and acute rejection (AR) among deceased donor kidney transplant recipients. The medical records of 111 patients who underwent kidney transplantation from deceased donors between November 1994 and July 2009 were retrospectively analyzed. DGF was observed in 54% of the patients and the prevalence of AR in the first year after transplantation was 9.9%. The incidence of DGF was higher among patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 0 publications
3
24
0
Order By: Relevance
“…23,40,41 In a study by Simforoosh and associates 42 that compared graft and patient survival among patients who underwent KT from deceased-vs living donors, no significant difference in 1-year graft and patient survival between living and cadaver donor KT was found. It should be noted, however, that kidney removal and recipient transplant were coordinated in a way that cold ischemia time (CIT) was less than 3 hours.…”
Section: Discussionmentioning
confidence: 97%
“…23,40,41 In a study by Simforoosh and associates 42 that compared graft and patient survival among patients who underwent KT from deceased-vs living donors, no significant difference in 1-year graft and patient survival between living and cadaver donor KT was found. It should be noted, however, that kidney removal and recipient transplant were coordinated in a way that cold ischemia time (CIT) was less than 3 hours.…”
Section: Discussionmentioning
confidence: 97%
“…Systolic hypertensive blood pressure (BP) as well as proteinuria are strong and independent predictive factors for graft survival in paediatric patients [47][48][49][50]. CIT represents an independent risk factor for delayed graft function [51,52]. As the Values are given as mean AE SD, median (min; max), or as absolute counts (percentage).…”
Section: Discussionmentioning
confidence: 99%
“…This finding was matched with some reports denoting that slow and delayed graft function are risk factors for T-cell and antibodymediated rejection 19 and the combination of both can affect patient survival. 20,21 Most of our patients were young females, and this was explained by Dörje and associates 2 who found that most of their patients with rejection were young and nonadherent with suboptimal immuno suppression.…”
Section: Discussionmentioning
confidence: 99%